The Goat Farming Sector: Niche Opportunities for Romanian Farmers in Europe - Petre Adrian Liptac; Mihaela Pila; Silvius Stanciu (Journal of Agriculture and Rural Development Studies)
The paper proposes an analysis of the goat farming sector in Romania within the broader European context. The research is based on open access articles and data from Eurostat, the National Institute of Statistics, the International Goat Association, and Worldostats. The study highlights a positive evolution in Romania's goat farming sector, driven by European support measures and increasing international demand for goat meat. Despite this growth, domestic consumption remains low compared to other European countries, primarily limited to festive occasions. Structural challenges, including the lack of slaughtering and processing facilities, encourage live animal exports, which generate limited added value. Coupled payment support plays a vital role in sustaining goat farming activities, particularly for large farms, while its absence significantly increases the risk of small farm abandonment, threatening the sector's diversity and its contribution to the rural economy. To enhance domestic consumption and sector development, the study recommends targeted promotional campaigns on the nutritional benefits of goat products, infrastructure investments, and improved market organization. These measures aim to align Romania's goat farming sector with European best practices and unlock its full economic potential.